2003
DOI: 10.1002/pmic.200300465
|View full text |Cite
|
Sign up to set email alerts
|

An approach to remove albumin for the proteomic analysis of low abundance biomarkers in human serum

Abstract: Proteomic technologies are being used to discover and identify disease-associated biomarkers. The application of these technologies in the search for potential diagnostic/prognostic biomarkers in the serum of patients has been limited by the presence of highly abundant albumin and immunoglobulins that constitute approximately 60-97% of the total serum proteins. The purpose of the study was to evaluate whether treatment of human serum with Affi-Gel Blue alone or in combination with Protein A (Aurum serum protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
140
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(147 citation statements)
references
References 7 publications
5
140
0
2
Order By: Relevance
“…Recently, we have demonstrated that the use of AffiGel Blue and Aurum kit (Bio Rad Laboratories, USA) results in the removal of highly abundance albumin and simultaneously enhances the detection of several low abundance proteins (Ahmed et al, 2003). In this study, we used columns containing a mixture of Affi-Gel Blue and protein A (5 : 1) that is equally effective in removing high abundance albumin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we have demonstrated that the use of AffiGel Blue and Aurum kit (Bio Rad Laboratories, USA) results in the removal of highly abundance albumin and simultaneously enhances the detection of several low abundance proteins (Ahmed et al, 2003). In this study, we used columns containing a mixture of Affi-Gel Blue and protein A (5 : 1) that is equally effective in removing high abundance albumin.…”
Section: Discussionmentioning
confidence: 99%
“…The spin columns containing a mixture of Affi-Gel Blue and Protein A selectively bind and remove albumin and immunoglobulin (Ahmed et al, 2003). The spin columns were washed twice with 1 ml of binding buffer (20 mM phosphate buffer, pH 7.0) by centrifugation for 20 s at 1000 g. In all, 50 ml of serum was added to 150 ml of binding buffer and mixed by vortex and loaded on the spin columns.…”
Section: Affi-gel Blue and Protein A Treatmentmentioning
confidence: 99%
“…However, the binding of albumin to Cibacron blue dyes is nonspecific, and the sensitivity and specificity are not as effective as mAb-based immunoaffinity resin or columns [15][16][17][18]. Removal of IgG can be realized with Protein G resins or columns [15][16][17][18][19][20]. Comparing to Cibacron blue dye and Protein G methods, immunoaffinity depletion using multiple affinity removal columns (MARC) is more effective because it can simultaneously remove multiple abundant proteins, with minimal carryover, high longevity, and minimal nonspecific binding [16,17,21,22].…”
Section: Depletion Of Highly Abundant Proteinsmentioning
confidence: 99%
“…The Cibacron blue dye method is a traditional way to deplete albumin. However, the binding of albumin to Cibacron blue dyes is nonspecific, and the sensitivity and specificity are not as effective as mAb-based immunoaffinity resin or columns [15][16][17][18]. Removal of IgG can be realized with Protein G resins or columns [15][16][17][18][19][20].…”
Section: Depletion Of Highly Abundant Proteinsmentioning
confidence: 99%
“…4 In combination with mass spectrometry techniques, 2-DE is important in proteomics research for the discovery and identification of disease-associated markers. 5 In this study, we investigated the presence of P. falciparum proteins in the serum of malaria patients with the aim of identifying circulating proteins that may be useful as markers for diagnosis. Serum samples were depleted and analyzed using two approaches: direct mass spectrometry analysis and 2-DE followed by western blot and mass spectrometry.…”
Section: Introductionmentioning
confidence: 99%